Redescription of Ryukyua circularis (Pillai, 1954) (Isopoda, Cymothoidae), parasite of the Bleeker smoothbelly sardinella Amblygaster clupeoides Bleeker, 1849 from India - Vigneshwaran, P.; Ravichandran, S.; Martin, Melissa B. (Zootaxa, 2018)
Ryukyua circularis (Pillai, 1954) is recorded here for the first time on the host Amblygaster clupeoides Bleeker, 1849 from Indian waters. The species is redescribed with illustrations of the gravid female, adult male and manca from its type locality, and the known hosts and geographical records of the species are reviewed. Ryukyua circularis is readily identified from the oval to rounded body shape, widest at pereonite 3–5; cephalon deeply immersed in pereonite 1; mandible palp with the spiny surface, article 3 with a long terminal setae; pleonite 1–3 partially overlapped by a posterolateral margin of pereonite 7; pleotelson anterior lateral margins weakly convex, posterior margin evenly rounded, without median point.